Drivers and Management of Nutrient Overload in Dams: Insights from Roodeplaat Dam, South Africa - Samkele Siphelele Mnyango; Melusi Thwala; Christoff Truter; Nkosinathi Goodman Xulu; Yolandi Schoeman; Paul Johan Oberholster (Hydrology)
Anthropogenic activities significantly threaten aquatic ecosystems, accelerating water quality deterioration through pollution, overexploitation, and habitat disturbance. Roodeplaat Dam in South Africa exemplifies these challenges, experiencing nutrient overload driven by malfunctioning wastewater treatment works (WWTWs), urban runoff, and agricultural activities. This study investigates the spatio–temporal dynamics of flow patterns and nutrient loads in Roodeplaat Dam, focusing on the interplay between nutrient pollution, land use, and land cover change (LULCC). A multi-site sampling approach was employed to assess total phosphorus (TP) and nitrate–nitrite (NO3 + NO2) loading, complemented by geospatial analysis of LULCC impacts over two decades. The study revealed that TP and NO3 + NO2 concentrations surpassed permissible limits at certain monitoring sites, particularly downstream of WWTWs during low-flow periods, demonstrating their substantial role in elevating nutrient levels. The study further revealed that extensive human-driven changes in the catchment area were key contributors to nutrient dynamics. These changes included a reduction in vegetation cover from 65% to 45.17%, an increase in soil exposure from 10.25% to 22.01%, and urban expansion from 26.56% to 32.32%. These alterations disrupt natural nutrient cycles, leading to increased runoff and potential eutrophication of water bodies. Thus, to address these challenges, this study underscores the need for an integrated strategy that combines nature-based solutions, enhanced wastewater treatment, stricter regulatory compliance, and adaptive management to mitigate pollution and improve water resource sustainability. The insights gained from this case study provide valuable guidance for managing similar systems in developing regions under increasing anthropogenic and climatic pressures.